Clinical classification criteria for nonspecific low back pain: A Delphi-survey of clinical experts. (April 2018) - Dewitte, Vincent; De Pauw, Robby; De Meulemeester, Kayleigh; Peersman, Wim; Danneels, Lieven; Bouche, Katie; Roets, Arne; Cagnie, Barbara
Abstract: Background: Nonspecific low back pain (NSLBP) is a common problem. Attempts have been made to classify NSLBP patients into homogenous subgroups. Classification systems based on identifying the underlying mechanism(s) driving the disorder are clinically useful to guide specific interventions. Objective: To establish consensus among experts regarding clinical criteria suggestive of a dominance of 'articular', 'myofascial', 'neural', 'central', and 'sensorimotor control' dysfunction patterns (DPs) in NSLBP patients. Study design: A 2-phase sequential design of a focus group and Delphi-study. Methods: A focus group with 10 academic experts was organized to elaborate on the different DPs discernible in LBP patients. Consecutively, a 3-round online Delphi-survey was designed to obtain consensual symptoms and physical examination findings for the 5 DPs resulting from the focus group. Results: Fifteen musculoskeletal physical therapists from Belgium and the Netherlands experienced in assessing and treating LBP patients completed the Delphi-survey. Respectively, 34 (response rate, 100.0%), 20 (58.8%) and 15 (44.12%) respondents replied to rounds 1, 2 and 3. Twenty-two 'articular', 20 'myofascial', 21 'neural', 18 'central' and 11 'sensorimotor control' criteria reached a predefined ≥80% consensus level. For example, after round 2, 85.0% of the Delphi-experts agreed to identify 'referred pain below the knee' as a subjective examination criterion suggestive for a predominant 'neural DP'. Conclusion: These indicators suggestive of a clinical dominance of the proposed DPs could help clinicians to assess and diagnose NSLBP patients. Future reliability and validity testing is needed to determine how these criteria may help to improve physical therapy outcome for NSLBP patients. Highlights: A Delphi-study on clinical criteria in nonspecific LBP patients was performed. Based on pain mechanisms, 5 dysfunction patterns were used to subgroup patients. 44 subjective and 33 physical examination criteria reached a 80% consensus level. Future reliability and validity studies are needed to ascertain the diagnostic value.